Peningkatan Produktivitas Kelompok UKM Suvenir Desa Pematang Johar, Kabupaten Deli Serdang - Salam Irianto Nadeak; Yusmar Ali; Komda Saharja; Faudunasokhi Telaumbanua; Suhendra Suhendra; Siti Aisyah (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
Partners for this Community Service program are the Pematang Johar souvenir SME Group/Community, which has 20 members. From the results of discussions with SME partners, it was agreed to solve problems: knowledge related to entrepreneurship, printing/screen printing skills, creativity in screen printing processing that has sales power, building various designs, engineering digital devices, how to do services and trading online systems. Based on the explanation above, in dealing with the difficulties faced by the Pematang Johar souvenir SME Group, it was mutually agreed on the need to provide knowledge and motivation to the SME Group about the importance of entrepreneurship for the future. printing/screen printing skills training. Provide training on t-shirt screen printing production techniques in a comprehensive manner. Facilitate the tools needed for training. screen printing processing creativity that has selling power. create various types of designs using computer applications. use of digital tools. and seeking services and commerce online and using social media. Service results show improvement in terms of: Entrepreneurial understanding, knowledge of production techniques, knowledge of production tools, production quality, design skills, Life Welfare, online marketing techniques, digital printing knowledge, digital printing skills